Analysis of digital contact tracing technologies employed during COVID-19 Pandemic - Kainyu, Fridah; Mwadulo, Mary (African Journal of Science, Technology and Social Sciences, 2022)
Corona virus (COVID-19) is a worldwide pandemic that was first reported in Wuhan, China 2019.The virus claimed lives and negatively changed the mobility patterns of humans. As a measure to control the spread of the virus, Digital Contact Tracing Technologies (DCTTs) were employed to contain the virus. The (DCTTs) are used to track and notify users digitally about their interactions with infected individuals and help strengthen health service systems. The most widely used Digital Contact Tracing Technologies include those that use Global Positioning, Bluetooth, Quick Response (QR) Codes and Wireless Fidelity (Wi-Fi). These technologies depend on monitoring symptoms, mobility of a person, location and proximity of individuals. This paper reviews literature by analyzing the Digital Contact Tracing Technologies (DCTTs) employed for COVID-19 through a desk study. The review highlights the advantages and disadvantages of using these technologies, with an aim of recommending ways in which the technologies can be used to attain maximum benefit.